2015
DOI: 10.1097/ypg.0000000000000065
|View full text |Cite
|
Sign up to set email alerts
|

Melanocortin-4 receptor gene variants are not associated with binge-eating behavior in nonobese patients with eating disorders

Abstract: We aimed to determine whether variability in the melanocortin-4 receptor (MC4R) gene, predisposing to hyperphagia and obesity, may also be present in nonobese patients with binge-eating behavior or be related to anthropometric or psychopathological parameters in these patients. The coding region of the MC4R gene was sequenced in nonobese patients with binge-eating behavior diagnosed with bulimia nervosa or binge-eating disorder (n=77); individuals with severe early-onset obesity (n=170); and lean women with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…BED prevalence rates are reportedly elevated in this demographic, in contrast with the general population . We acknowledge that BED afflicts non‐obese as well as obese populations and that our study of the effect of GOF mutations on BED in individuals with obesity is limited in its generalizability.…”
Section: Discussionmentioning
confidence: 82%
“…BED prevalence rates are reportedly elevated in this demographic, in contrast with the general population . We acknowledge that BED afflicts non‐obese as well as obese populations and that our study of the effect of GOF mutations on BED in individuals with obesity is limited in its generalizability.…”
Section: Discussionmentioning
confidence: 82%
“…The possibility of a single gene having both loss of function and gain of function mutations is supported by recent findings on MC4R and the 16p locus where loss of function mutations/deletions lead to hyperphagic obesity while gain of function mutations/duplications lead to leanness and selective/restrictive eating behaviors [93,97,[131][132][133]. However, several studies have reported contradictory results on the association between binge eating behavior and loss of function variants in MC4R [134][135][136]; and gain of function variants in MC4R are not more frequent in AN patients than in the general population [137]. Analyzing whole-genome SNP array and whole-exome sequencing data and searching for complex patterns of mirror CNVs or enrichment in loss of function and gain of function mutations in ANBP cases may identify promising candidate genes that may be further validated in ANR, BN, or BED cases.…”
Section: Mutations/structural Gene Variations With Oppositementioning
confidence: 49%
“…Indeed, later reports have been unable to reproduce such association in obese individuals [120][121][122][123][124]. Furthermore, very recently we and others have expanded these negative findings to nonobese patients with AN or BN [125,126]. In addition, BMI-related MC4R SNPs have also been related with certain kind of feeding behaviors in the general population [124].…”
Section: Perspective Gervasini and Gamero-villarroelmentioning
confidence: 83%
“…Mutations in the MC4R gene were not associated with binge-eating behavior in nonobese ED patients [125] Stutzmann et al rs17782313-C allele OB = 2383; Controls = 10489…”
Section: Mutation Screening By Sequencingmentioning
confidence: 97%
See 1 more Smart Citation